Efficient Killing of Murine Pluripotent Stem Cells by Natural Killer (NK) Cells Requires Activation by Cytokines and Partly Depends on the Activating NK Receptor NKG2D - Gröschel, Carina; Hübscher, Daniela; Nolte, Jessica; Monecke, Sebastian; Sasse, André; Elsner, Leslie; Paulus, Walter; Trenkwalder, Claudia; Polić, Bojan; Mansouri, Ahmed; Guan, Kaomei; Dressel, Ralf (Frontiers in Immunology, 2017)
Natural killer (NK) cells play an important role as cytotoxic effector cells, which scan the organism for infected or tumorigenic cells. Conflicting data have been published whether NK cells can also kill allogeneic or even autologous pluripotent stem cells (PSCs) and which receptors are involved. A clarification of this question is relevant since an activity of NK cells against PSCs could reduce the risk of teratoma growth after transplantation of PSC-derived grafts. Therefore, the hypothesis has been tested that the activity of NK cells against PSCs depends on cytokine activation and specifically on the activating NK receptor NKG2D. It is shown that a subcutaneous injection of autologous iPSCs failed to activate NK cells against these iPSCs and can give rise to teratomas. In agreement with this result, several PSC lines, including two iPSC, two embryonic stem cell (ESC) and two so-called multipotent adult germline stem cell (maGSC) lines, were largely resistant against resting NK cells although differences in killing were found at low level. All PSC lines were killed by interleukin (IL)-2-activated NK cells and maGSCs were better killed than the other PSC types. The PSCs expressed ligands of the activating NK receptor NKG2D and NKG2D-deficient NK cells from Klrk1-/- mice were impaired in their cytotoxic activity against PSCs. The low cytotoxic activity of resting NK cells was almost completely dependent on NKG2D. The cytotoxic activity of IL-2-activated NKG2D-deficient NK cells against PSCs was reduced, indicating that also other activating receptors on cytokine-activated NK cells must be engaged by ligands on PSCs. Thus, NKG2D is an important activating receptor involved in killing of murine PSCs. However, NK cells need to be activated by cytokines before they efficiently target PSCs and then also other NK receptors become relevant. These features of NK cells might be relevant for transplantation of PSC-derived grafts since NK cells have the capability to kill undifferentiated cells, which might be present in grafts in trace amounts.